SOA : separating myth from reality using the facts to lead the SOA journey. - Potts, Mark
There is still enough hype around service-oriented architecture (SOA) that it's difficult to get a handle on the realities of implementation. While most IT managers now understand what an SOA can do for IT, many still need help figuring out how to get started. New questions about management, reuse and legacy applications are also emerging as more and more companies think about how to adopt SOA solutions.